"You Have to Look at Finances as a Joint Venture, Whether or Not You Have a Joint Account": Exploring Strategies Couples Use to Successfully Communicate About Money. Issue 5 (4th July 2021) - Bourdeaux, Renee; Bright, Maggie
Abstract: Disagreements surrounding finances often impact relationships and may even lead to divorce. Financial conversations, then, emerge as the strongest "tug-of-war" opponent to the successful partnership couples hope to achieve, so researchers must identify strategies to positively talk about money. This study seeks to identify communication strategies married partners employ to successfully discuss money. This study takes an exploratory approach utilizing open-ended surveys. The narratives from 53 participants revealed that couples enact the maintenance strategies of understanding, sharing tasks, relationship talks, and self-disclosure to achieve positive financial conversations. Moreover, because one-third of the data focused on the importance of establishing rules and goals, couples should make it a priority to set clear rules and goals for their conversations revolving around money.